Glycosaminoglycans and vitamin C in ovo feeding affects bone characteristics of chicks - Santos, Elaine Talita [UNESP]; Sgavioli, Sarah; Correa Castiblanco, Diana Maryuri [UNESP]; Faria Domingues, Carla Heloisa de; Oliveira de Quadros, Thays Cristina [UNESP]; Borges, Liliana Longo [UNESP]; Petrolli, Tiago Goulart; Baraldi-Artoni, Silvana Martinez [UNESP] (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2018)
Different levels of glycosaminoglycans (chondroitin sulfate and glucosamine sulfate) and vitamin C were injected in ovo to determine whether additive use influences the incubation parameters and bone characteristics of posthatch chicks. Hatchability was not affected by addition of glycosaminoglycans and vitamin C in ovo. However, chicks that received 4 ug additive showed 2.86% reduction in total mortality when compared with chicks from non-injected eggs. Moreover, tibia area and femur bone mineral density increased in chicks from eggs injected with 2.16 and 6.00 mu g of additive, respectively. In ovo feeding with glycosaminoglycans and vitamin C can benefit bone development in embryos and reduce total mortality during the incubation period.
Keywords: ascorbic acid; bone mineral density; bone strength; chondroitin; glucosamine